The overweight patient : a psychological approach to understanding and working with obesity (London : Jessica Kingsley, 2006)
Contents include: obesity and therapy; cultural and parent influences on decisions regarding weight; clinical considerations in working with the overweight patient; losing weight, maintaining loss and regaining weight; inquiry and diagnosis; ego states; the parent ego state; the child ego state; the adult ego state; psychological hungers; games; the creation of the body and eating functions as defence structures.